Maternal cerebellar gray matter volume is associated with daughters' psychotic experience. Issue 7 (11th May 2020) - Hashimoto, Naoki; Michaels, Timothy I.; Hancock, Roeland; Kusumi, Ichiro; Hoeft, Fumiko
Abstract : Aim: A substantial portion of children and adolescents show subthreshold psychotic symptoms called psychotic experience (PE). Because PE shares its biological and environmental risk factors with psychotic spectrum disorders, parental neuroanatomical variation could reflect a heritable biological underpinning of PE that may predict an offspring's PE. Methods: A total of 94 participants from 35 families without a diagnosis of major neuropsychiatric disorders were examined, including 14 mother–daughter, 17 mother–son, 12 father–daughter, and 16 father–son dyads. An offspring's PE was assessed with the Atypicality subscale of the Behavior Assessment System for Children – 2nd Edition, Self‐Report of Personality form (BASCaty). We examined correlations between voxel‐by‐voxel parental gray matter volume and their offspring's BASCaty score. Results: Maternal cerebellar gray matter volume using voxel‐based morphometry was positively correlated with their daughters' BASCaty scores. The findings were significant in a more robust approach using cerebellum‐specific normalization known. We did not find significant correlation between paternal gray matter volume and BASCaty scores or between offspring gray matter volumes and their BASCaty scores. Conclusion: Expanding upon parent‐of‐origin effects in psychosis, maternal neuroanatomical variation was associated with daughters' PE. The nature of this sex‐specific intergenerational effect is unknown, but maternally transmitted genes may relate cerebellum development to PE pathogenesis.